Association Between Single Nucleotide Polymorphisms in PPARA and EPAS1 Genes and High-Altitude Appetite Loss in Chinese Young Men - Pan, Wenxu; Liu, Chuan; Zhang, Jihang; Gao, Xubin; Yu, Shiyong; Tan, Hu; Yu, Jie; Qian, Dehui; Li, Jiabei; Bian, Shizhu; Yang, Jie; Zhang, Chen; et al. (Frontiers in Physiology, 2019)
Appetite loss is a common symptom that occurs in high altitude (HA) for lowlanders. Previous studies indicated that hypoxia is the initiating vital factor of HA appetite loss. PPARA, EPAS1, EGLN1, HIF1A, HIF1AN and NFE2L2 play important roles in hypoxic responses. We aimed to explore the association of these hypoxia-related gene polymorphisms with HA appetite loss. In this study, we enrolled 416 young men who rapidly ascended to Lhasa (3700 m) from Chengdu (<500m) by plane. PPARA, EPAS1, EGLN1, HIF1A, HIF1AN and NFE2L2 were genotyped by MassARRAY. Appetite scores were measured to identify HA appetite loss. Logistic regression and multiple genetic models were tested to evaluate the association between the single nucleotide polymorphisms (SNPs) and risk of HA appetite loss in crude and adjusted (age and SaO2) analysis. Subsequently, Haploview software was used to analyze the linkage disequilibrium (LD), haplotype construction and the association of diverse haplotypes with the risk of HA appetite loss. Our results revealed that allele “A” in PPARA rs4253747 was significantly associated with the increased risk of HA appetite loss. Codominant, dominant, recessive, and log-additive models of PPARA rs4253747 showed the increased risk of HA appetite loss in the crude and adjusted analysis. However, only dominant, overdominant, and log-additive models of EPAS1 rs6756667 showed the decreased risk of HA appetite loss in the crude and adjusted analysis. Moreover, the results from haplotype-based test showed that the rs7292407-rs6520015 haplotype “AC” was associated with HA appetite loss in the crude analysis rather than the adjusted analysis.In this study, we first established the association of SNPs in PPARA (rs4253747) and EPAS1 (rs6756667) genes with the susceptibility to HA appetite loss in Han Chinese young men. These findings provide novel insights into understanding the mechanisms involved in HA appetite loss.